2010
DOI: 10.1161/circresaha.110.216846
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Inhibits Vascular Calcification via Vascular RANKL System

Abstract: Key Words: RANKL Ⅲ vascular calcification Ⅲ BMP-2 Ⅲ MGP Ⅲ estrogen V ascular calcification is one of the major complications of cardiovascular disease and an independent risk factor for myocardial infarction and cardiac death, 1 among other outcomes. Arterial calcification is also associated with osteoporosis, especially in postmenopausal women. 2 Recent evidence strongly suggests the biological linkages on both disease mechanisms based on the presence of bone-related proteins 3 and bone-related cells at the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
68
0
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(87 citation statements)
references
References 52 publications
12
68
0
7
Order By: Relevance
“…The relationship in younger postmenopausal women is now well established; however, the paucity of studies in older postmenopausal women limits our understanding of E2 effects in this context, although studies are now addressing this issue. 36,37 Replicating the postmenopausal state in animal models is challenging, and E2 replacement after ovariectomy elicits dramatic effects on plaque progression and lipid profiles 27 ; thus, such studies tend to replicate findings in studies of younger postmenopausal women. The use of gonadally intact animals, by us and others, 38 avoids the need to interpret the E2 effect on total plaque area caused by altered plasma cholesterol levels; however, the limitation associated with use of intact animals is the pharmacological levels of E2 achieved in the blood.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The relationship in younger postmenopausal women is now well established; however, the paucity of studies in older postmenopausal women limits our understanding of E2 effects in this context, although studies are now addressing this issue. 36,37 Replicating the postmenopausal state in animal models is challenging, and E2 replacement after ovariectomy elicits dramatic effects on plaque progression and lipid profiles 27 ; thus, such studies tend to replicate findings in studies of younger postmenopausal women. The use of gonadally intact animals, by us and others, 38 avoids the need to interpret the E2 effect on total plaque area caused by altered plasma cholesterol levels; however, the limitation associated with use of intact animals is the pharmacological levels of E2 achieved in the blood.…”
Section: Discussionmentioning
confidence: 99%
“…25 However, other studies have demonstrated an inhibitory role for E2 in VSMC calcification in vitro. 26,27 In the context of atherosclerosis, studies support a protective effect of E2 on plaque calcification in women, based on the cardiovascular protective effects of E2 that reduce total plaque burden, attributable to modulation of traditional risk factors, such as plasma high-density lipoprotein and low-density lipoprotein. 28,29 In the clinic, studies show low serum E2 levels associate with increased coronary artery calcification (CAC), [30][31][32] whereas E2 replacement in younger menopausal women reduces CAC.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…At molecular level, estrogens down-regulate tumor necrosis factor (TNF)-α, which is found in both bone tissue and atheromas, and enhance VSMC calcification in vitro [79], and RANKL, which also plays a major role in both ectopic and physiologic calcification [80,81]. In addition, in cultured aortic VSMCs from adult ovariectomized pigs, 17β-estradiol, but not raloxifene, attenuated transdifferentiation induced by a calcifying medium and decreased the expression of bone sialoprotein [82].…”
Section: Estrogens and Sermsmentioning
confidence: 99%
“…[18][19][20] Vascular calcification and osteoporosis are both active biological processes, which share common mechanisms, including the BMP pathway, Wnt Pathway, and OPG. 15,21,22 Osteogenic bone formation in the heart has become the third axis in the triad hypothesis of CAVD as shown in the Figure. However, the role of statins in the field of CAVD has been elusive. All of the randomized clinical trials have been negative to date.…”
mentioning
confidence: 99%